PENENTUAN LOKASI BASIS DAN NON BASIS PENYEBARAN VIRUS CORONA (COVID-19) MENGGUNAKAN METODE LOCATION QUOTIENT (LQ) - Toto Iswanto; Maya Widyastiti (EKOLOGIA, 2022)
The corona virus pandemic that has hit the entire world is a threat to the order of people’s lives in all field so it must be solved quickly. This study aims to determine the location of the Basic and non-Basic of the spread of corona virus in Lubuk Besar district, Province of Bangka Belitung Island. Data used is this study are the number of population and the number of COVID-19 cases in Lubuk Besar district, Bangka Belitung Province. This research is a descriptive type of research with a quantitative approach using the Location Quotient Method. The results showed that in January 2021 there are 4 villages that became the basis location for the spread of the corona virus, i.e. Kulur Village with LQ value is 1.634581, Kulur Ilir Village with LQ value  is 1.618289, Lubuk Besar Village with LQ value is 1.914148, and Perlang Village with LQ value is 1.412130, and the other villages are non-basic. In February 2021 the villages that became the basis are Kulur Ilir Village with LQ value is 1.182939, Perlang Village with LQ value is 1.376094, and Trubus Village with LQ value is 2.996931, and the other villages are non-basic location. In March 2021, Perlang Village with LQ value is 1.184505 and Trubus Village with LQ value is 5.600585 became the basis for the spread of the corona virus, and the other villages are non-basic location.